Global trends in sustainability policies in higher education - Nogueiro, T.; Saraiva, M.; Chaleta, E (Management in higher education for sustainability, 2025)
Higher education institutions (HEis) around the world have played a crucial role in promoting sustainable practices. Global sustainability policies gain importance, providing guidelines and principles that can lead these institutions towards a more sustainable management. There are several main international docu ments and guidelines, such as the UN 2030 Agenda, UNESCO guidelines and the UN Global Pact. In the context of higher education, the sustainable development goals play a relevant role, guiding institutions to incorporate sustainability into research, education and campus operations. The implementation of sustainability policies in HEis varies considerably depending on the geographical and institutional context and the resources available. This study identifies and analyses critical success factors (CSFs) and challenges associated with the implementation of sustainability policies in HEis. Successful case studies demonstrate that a strong leadership, inter disciplinary research and collaborative partnerships can drive transformative change. Global trends in sustainability policies point out to an increasing emphasis on inter disciplinary research, promoting collaborative efforts totackle complex sustainability problems. Sustainability for HEls is apath of no return once started. These institutions are no longer just seen as entities that possess knowledge, but as entities that can use that knowledge to be sustainable and pass on to others the principles of preserving what is the future of society and the planet, taking an active part in sustainable development.